The Colonization and conquest of the Philippines by Spain : (Filipiniana Book Guild, 1965)
The documents in this lolume were written by the actors of that great drama of conquest and Christianization. Contents: letter from Philip II to Luis de Velasco, Letter from Philip II to Andres de Urdaneta, ...